2009
DOI: 10.1016/j.juro.2008.10.104
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Isoforms That Mediate Estrogen and Progestagen Action in the Female Lower Urinary Tract

Abstract: Word count (text): 2,500Word count (abstract): 246 2 Abstract PurposeBladder symptoms can be ameliorated by sex steroids but the mechanism of action is unknown. Previous work examining steroid receptor expression in the bladder did not examined receptor subtype expression. We now report the distribution of estrogen (ER , ER ) and progesterone receptor isoforms (PR-A, PR-B) in the female lower urinary tract. Materials & methodsProspectively recruited women undergoing routine urogynaecological or gynaecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
0
38
0
3
Order By: Relevance
“…The bladders of mice exhibit down-regulation of ER in the urethral epithelium and the SMC in contrast with controls, but we did not find expression of ER in the bladder urothelium of controls and Sh-treated mice. In accordance, ER was found to localize to the urethral epithelium but has been reported to be absent from the transitional epithelium (8).…”
Section: Discussionmentioning
confidence: 55%
“…The bladders of mice exhibit down-regulation of ER in the urethral epithelium and the SMC in contrast with controls, but we did not find expression of ER in the bladder urothelium of controls and Sh-treated mice. In accordance, ER was found to localize to the urethral epithelium but has been reported to be absent from the transitional epithelium (8).…”
Section: Discussionmentioning
confidence: 55%
“…Estrogen receptors are present in the lower urinary tract of animals 8 as well as in humans, 9 and play an important role for LUT function, both normally and in LUT dysfunction. 10 Epidemiological studies have shown that the development of LUTS in postmenopausal women is associated with the onset of estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…72 ER was found to localize to the urethral epithelium but has been reported to be absent from transitional epithelium. 73 The knowledge that schistosomes have estradiol receptors as long been attained. 74 This molecule able to bind estradiol has been previously described in schistosomes.…”
mentioning
confidence: 99%